2018
DOI: 10.1097/ta.0000000000001971
|View full text |Cite
|
Sign up to set email alerts
|

A subset of five human mitochondrial formyl peptides mimics bacterial peptides and functionally deactivates human neutrophils

Abstract: Therapeutic, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 19 publications
2
44
0
Order By: Relevance
“…Accompanying the impairment we observed in ex vivo NET formation was a significant trauma-induced elevation in the circulating levels of the mitochondrial-derived N-formylated peptide ND6. In a recent study, suppressed chemotactic responses toward CXCL1 and LTB 4 were reported for neutrophils pre-treated with synthetic ND6 (22), a finding that mirrored results of previous studies where prior exposure to bacterial-derived N-formylated peptides or ND6 respectively was shown to reduce neutrophil migration and ROS production upon secondary stimulation (10, 26). Adding to this growing body of literature that suggests a tolerising effect for mitochondrial-derived peptides on neutrophil function, we demonstrated that neutrophils pre-treated with whole mtDAMP preparations, but not purified mtDNA, exhibited significantly reduced NET production following PMA stimulation.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Accompanying the impairment we observed in ex vivo NET formation was a significant trauma-induced elevation in the circulating levels of the mitochondrial-derived N-formylated peptide ND6. In a recent study, suppressed chemotactic responses toward CXCL1 and LTB 4 were reported for neutrophils pre-treated with synthetic ND6 (22), a finding that mirrored results of previous studies where prior exposure to bacterial-derived N-formylated peptides or ND6 respectively was shown to reduce neutrophil migration and ROS production upon secondary stimulation (10, 26). Adding to this growing body of literature that suggests a tolerising effect for mitochondrial-derived peptides on neutrophil function, we demonstrated that neutrophils pre-treated with whole mtDAMP preparations, but not purified mtDNA, exhibited significantly reduced NET production following PMA stimulation.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, we showed that the trauma-induced reduction in NET formation could be replicated in vitro by treating neutrophils isolated from healthy donors with mtDAMPs prior to secondary stimulation. Thus, our data provides support for the emerging concept of mtDAMP-induced tolerance, where the post-injury release of mtDAMPs into the circulation has been proposed to contribute to the neutrophil dysfunction that develops in the aftermath of traumatic injury (10, 22).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Mitochondrial DAMPs induce Ca 2+ signaling and MAPK activation in human neutrophils, mediate chemotaxis and activation of the oxidative burst, promote the release of MMP-9 and CXCL8 by these cells, and may suppress cellular responses to CXCL1, LTB 4 and fMLF. 97,98 Mitochondrial DAMPs were abundantly present in bronchoalveolar fluids and serum from patients with acute respiratory distress syndrome, and deficiency or inhibition of FPR1 resulted in reduced inflammation in a murine model of this disease. 99 Additionally, high levels of mitochondrial DAMPs were associated with the development of primary graft dysfunction in lung transplantation patients.…”
Section: C5ar1mentioning
confidence: 99%